2009
DOI: 10.1007/s10660-009-9038-0
|View full text |Cite
|
Sign up to set email alerts
|

IT governance challenges in a large not-for-profit healthcare organization: The role of intranets

Abstract: This paper reports on the implementation of IT governance in a not-forprofit healthcare organization and considers how managerial strategies for this governance relate to the progressive management approach commonly called the Horizontal Organization. Discussion includes how IT governance was implemented and the mechanisms by which power and politics in the organization were harnessed to achieve strategic goals. In this case study, CEO support for IT governance was related principally to the need for fiscal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Typically, IT governance researchers (such as Van Grembergen et al, 2003;Merhout and Havelka, 2008) have proposed the use of Control Objectives for Information and related Technology (CoBIT), Information Technology Infrastructure Library (ITIL) and IT Balanced scorecard to provide more detailed guidelines and best practice standards so that better alignment between IT and organizational strategy can be achieved. The last aspect focuses on the relational characteristic of IT governance which entails critical factors such as commitment, involvement and trust (De Haes and Van Grembergen, 2004;Wilkin and Riddett, 2009).…”
Section: It Governance Definedmentioning
confidence: 99%
“…Typically, IT governance researchers (such as Van Grembergen et al, 2003;Merhout and Havelka, 2008) have proposed the use of Control Objectives for Information and related Technology (CoBIT), Information Technology Infrastructure Library (ITIL) and IT Balanced scorecard to provide more detailed guidelines and best practice standards so that better alignment between IT and organizational strategy can be achieved. The last aspect focuses on the relational characteristic of IT governance which entails critical factors such as commitment, involvement and trust (De Haes and Van Grembergen, 2004;Wilkin and Riddett, 2009).…”
Section: It Governance Definedmentioning
confidence: 99%
“…Wilkin and Riddett [52] analyzed the implementation of some IT governance mechanisms in a not-for profit healthcare organization, finding that the use of project management frameworks helps the organization to manage IT resources and IT project performance. They still found that the use of communication mechanisms like the intranet system helped the organization to manage the IT projects and their performance.…”
Section: Figure 2 Research Model Resultsmentioning
confidence: 99%
“…Several mechanisms can be used to track and monitor the implementation of the IT strategy and IT projects, besides resources and related services of IT. They are SISP, SLA, business cases evaluation and IT chargeback systems, PMBok, CobiT and Internet Portal [1,15,21,33,52]. Based on these findings, we propose the following hypotheses:…”
Section: It Performance Managementmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, their finding also revealed that the organizations which performed ITG could generate profit up to 20% compared with non-ITG. Other studies have also addressed the important of ITG in several industries, including banking, health care, and public sectors [2,3,4]. However, there is a limited amount of research concerning the ITG practices in university.…”
Section: Introductionmentioning
confidence: 99%